Study on safety of Philippine National Railways grade crossing - Clarito, Albie F.; Ramos, Beverly May D.
Safety is one of the most important aspects of transportation. It is necessary to determine safety by evaluating if improvement exists based on the occurrence of accidents. In assessing the safety in PNR, accidents at the grade crossings should be analyzed since it is the weak point of a railway. Each railway was evaluated based on their existing characteristics namely: type of crossing, type of barrier, warning device, and the vehicle traffic volume. Using hazard indices, each characteristic was evaluated individually. Two-way crossing has higher hazard index compared to one-way crossing, full barriers also exhibited higher hazard compared to half barriers. In the case of warning device, crossings with two different sets of warning device on each direction have exhibited the highest hazard index and 30-40 thousand for the vehicle traffic volume. Using the chi-squared test, two combinations of characteristics passed the test. These are vehicle volume traffic presented in AADT versus Barrier Type and Alarm Device Type versus Crossing Type. An assessment of all the characteristics for specific crossings was also made to evaluate the hazard index of a specific crossing. Based on the results of the hazard indices, it is recommended that PNR, should consider using half-barriers instead of full barriers for the case of type of barriers and installation of alarm signal lamp which is the main difference between a type A and a type B warning device.